2006
DOI: 10.1598/rt.59.7.3
|View full text |Cite
|
Sign up to set email alerts
|

Oral Reading Fluency Norms: A Valuable Assessment Tool for Reading Teachers

Abstract: In 1992, the authors collaborated to develop a set of norms for oral reading fluency for grades 2–5. Since then, interest in and awareness of fluency has greatly increased, and Hasbrouck and Tindal have collaborated further to compile an updated and expanded set of norms for grades 1–8. This article discusses the application of these norms to three important assessment activities related to improving students' reading achievement: Screening students for possible reading problems Diagnosing deficits in student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
338
3
24

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(408 citation statements)
references
References 13 publications
11
338
3
24
Order By: Relevance
“…Barr et al 2002, p. 76. New speed norms for English (Hasbrouck and Tindal 2006) show the 50th percentile as 53 words per minute (spring of grade 1) and 89 words per minute 25. Laberge and Samuels in 1974 found that speed was a prerequisite for comprehension.…”
Section: Chaptermentioning
confidence: 99%
“…Barr et al 2002, p. 76. New speed norms for English (Hasbrouck and Tindal 2006) show the 50th percentile as 53 words per minute (spring of grade 1) and 89 words per minute 25. Laberge and Samuels in 1974 found that speed was a prerequisite for comprehension.…”
Section: Chaptermentioning
confidence: 99%
“…The total reading time was thus 8 minutes (480,000 milliseconds) per study phase. Reading fluency scores (Hasbrouck & Tindal, 2006) showed that this should be sufficient time for the students to carefully read each paragraph (i.e., 133 words per minute in grade 8). During the initial reading phases, the computer automatically went to the subsequent paragraph, whereas during the final reading phase (the final phase in both conditions), students were presented the complete text and could scroll through it as they liked.…”
Section: Study-test-condition; Sts)mentioning
confidence: 99%
“…Oral reading fluency is a measure of overall reading competence: the ability to translate letters into sounds, unify sounds into words, process connections, relate text to meaning, and make inferences to fill in missing information (Hasbrouck & Tindal, 2006). As skilled readers translate text into spoken language, they combine these tasks in a seemingly effortless manner (automaticity); because oral reading fluency captures this complex process, it can be used to characterize overall reading skill.…”
Section: Oral Reading Fluency (Paragraph Reading) With Comprehensionmentioning
confidence: 99%
“…(continued) , 1999;Hasbrouck & Tindal, 2006;Kame' enui et al, 2006;Kaminski et al, 2006). In many of these applications, relevant EGRA subtasks are complemented by a short series of contextual questions that help analysts break down results by groups of interest, such as socioeconomic status, parents' education or reading ability, language used in the home, reading materials found in the home, or other factors.…”
Section: Impact Evaluation (Chapter 3)mentioning
confidence: 99%
See 1 more Smart Citation